Effect of cooling system on Feed and Water Intake, Body Weight Gain and Physiological Responses of Murrah Buffaloes during Summer Conditions - SINGH, SOHANVIR; Hooda, O K; Narwade, Baban; Baliyan, Beenam; Upadhyay, R C (Indian Journal of Dairy Science, 2015)
Twelve Murrah buffalo heifers were selected and divided equally into two groups. Group-I (experimental) animals were kept under fan cum mist system and group-II (control) animals under normal ambient conditions. Dry and wet bulb temperatures were recorded throughout the study and THI was calculated. The Average dry bulb temperature was 33.09±0.37°C at 16.00 hrs under natural conditions. Mist cum fan system reduced dry bulb temperature by 2.21°C and wet bulb temperature by 1.55°C from their respective temperatures recorded under natural conditions. Physiological responses viz. rectal temperature, skin temperature, respiration rate and pulse rate of both groups were recorded at 9.00hrs and at 14.00hrs under both conditions. Overall average of RT was 100.76±015°F and 101.11±0.35°F at 9.00 hrs, which increased to 101.48±013°F and 102.75±0.29°F at 14.00 hrs in experimental and control groups, respectively.  Fan cam mist system lowered the RT by 1.27°F than natural conditions. ST of group-II was higher (98.49±0.42°F) than group-I (96.54±0.38°F) animals at 14.00 hrs. During afternoon, RR and PR were lower in group-II compared to group-I by 3 breaths /min and 4 beats /min, respectively. The body weight gain was significantly higher (p